Use of unit root methods in early warning of financial crises - Timo Virtanen; Eero Tölö; Matti Virén; Katja Taipalus (Bank of Finland, 2016)
Unit root methods have long been used in detection of financial bubbles in asset prices. The basic idea is that fundamental changes in the autocorrelation structure of relevant time series imply the presence of a rational price bubble. We provide cross-country evidence for performance of unit-root-based early warning systems in ex-ante prediction of financial crises in 15 EU countries over the past three decades. We then combine the identified early warning signals from multiple time series into a composite indicator. We also show that a mix of data with different frequencies may be useful in providing timely warning signals. Our results suggest and an early warning tool based on unit root methods provides be a valuable accessory in financial stability supervision.
URN:NBN:fi:bof-201611041478
Keywords: G01; G14; G21; 330